Analysis of end effect in ironless stator AFPM machine via MEC model. Issue 1 (6th December 2019) - Gao, Huamin; Zhang, Zhuoran; Wang, Chen; Geng, Weiwei; Liu, Ye
Abstract : The Halbach‐array permanent magnet (PM) rotors can achieve higher air‐gap flux density due to magnetic flux gathering effect, which contributes to the higher‐torque density improvement of the ironless stator axial flux PM (AFPM) machine. However, the end leakage fluxes of the ironless stator AFPM machine are serious due to the large magnetic resistance of the main flux loop in ironless stator machines. Circular arc straight line permeance model is adopted to calculate magnet‐to‐magnet and magnet‐to‐rotor end leakage fluxes based on the analysis of the relationship between end leakage fluxes and coils. A magnetic equivalent circuit (MEC) model is established considering end leakage fluxes. The leakage coefficients representing the ratio of end leakage fluxes to main flux and radial coefficients representing effective radial lengths of end leakage fluxes are analysed via the MEC model. The coefficients vary with machine parameters including PM thickness, rotor yoke thickness and air‐gap length. On the basis of the analysis results, the influence factors of end leakage fluxes are summarised and the 50 kW ironless stator AFPM machine is optimised. Finally, a 50 kW ironless stator AFPM machine with Halbach‐array PM rotors is prototyped to verify the results of the finite element analysis and MEC model.